2007
DOI: 10.1089/acm.2007.6250
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Effect of Unilateral Electroacupuncture on Muscle Strength

Abstract: Objectives: This study aimed to examine the bilateral effect of 4 weeks of unilateral electroacupuncture on leg muscle strength.Design: The effect of unilateral electroacupuncture at two selected acupoints, Zusanli (ST-36) and Xiajuxu (ST-39), which are located on the anterior tibialis muscle, on dorsiflexion strength was evaluated by statistical analyses of the interactions between the muscle strength pre and post 4 weeks of intervention, between the two legs, and between an experimental and a control group.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 34 publications
3
36
0
1
Order By: Relevance
“…Results indicate that acupuncture was able to significantly and immediately increase gain of handgrip strength measured by the dynamometer. This result is consistent with the studies of Yim et al (2007) and Huang et al (2007) who concluded that there are ergogenic effects of some acupoints. It is possible that the lost of strength found in GCRT may be due to muscle relaxation, considering that the volunteers of this group received no intervention.…”
Section: Discussionsupporting
confidence: 93%
“…Results indicate that acupuncture was able to significantly and immediately increase gain of handgrip strength measured by the dynamometer. This result is consistent with the studies of Yim et al (2007) and Huang et al (2007) who concluded that there are ergogenic effects of some acupoints. It is possible that the lost of strength found in GCRT may be due to muscle relaxation, considering that the volunteers of this group received no intervention.…”
Section: Discussionsupporting
confidence: 93%
“…Electric stimulation has been widely used as a supplementary training method for improving muscular strength and fitness as well as a means of rehabilitation (Maffiuletti, 2010;Paillard, 2008). Electroacupuncture has recently been shown to be able to improve muscle strength as well (Huang et al, 2007). Although the electric stimulation and electroacupuncture can directly activate peripheral nerve and muscle fibres and by-pass the central nervous system, recent evidence has suggested that the training/therapeutic effects of electric stimulation may also include neural plasticity (Chae et al, 2008;Maffiuletti, 2010;Wolpaw, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be similar to the concept of cross education. A recent investigation in our laboratory has demonstrated that four weeks of electroacupuncture on tibialis anterior muscle (TA) of one limb can significantly increase dorsiflexion muscle strength in both the stimulated limb and the contralateral limb (Huang et al, 2007). The exact mechanism of cross education is not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Moreover, Huang et al demonstrated that the dorsi and plantar flexion strengths of the ankle improved by 21.3% following a 4-week acupuncture treatment compared with another ankle without any treatment. 6 Larisa et al also reported increased isometric strength and electromyography (EMG) activation after acupuncture stimulation. 7 Nevertheless, studies on the immediate effects of one-time acupuncture treatment that is directly applied in the field on the muscles of athletes are still significantly lacking.…”
mentioning
confidence: 98%